Private tutoring, students' cognitive ability and school engagement, and the formal schooling context: Evidence from middle school students in China. (April 2018) - Zhang, Yueyun
This study examines the effects of participation in private tutoring on Chinese students' cognitive ability and school engagement, and further investigates the role of the formal schooling context in moderating these effects. Utilizing a nationally representative data set of Chinese middle school students and the method of propensity score matching, I find that participation in private tutoring significantly boosts students' cognitive ability and school engagement. Moreover, multilevel models are employed to demonstrate that the observed positive effects of receiving private tutoring vary across schools. Specifically, these effects are more significant for students in low-quality schools and tend to decrease for students in higher-quality schools. This study thus calls for a systematic examination of the private tutoring effects on various dimensions of student development as well as the contextual influence of formal schools while discussing the implications of private tutoring for educational inequality in contemporary China.